Difference between arterial and venous peak optical density after thrombectomy is associated with functional outcomes - Liu, Guangzhi; Cao, Jianghui; Zhou, Peiyang; Sun, Dong; Kang, Zhiming; Fan, Ruixue; Mei, Bin; Zhang, Junjian (Frontiers in neurology, 2024)
The density of contrast medium in digital subtraction angiography (DSA) have been used to evaluate the cerebral circulation function. Our aim was to study the effect of difference in arteriovenous peak optical density (POD) after thrombectomy on functional outcomes. Consecutive patients with acute ischemic stroke due to large vessel occlusion who underwent thrombectomy were reviewed. We processed DSA images with ImageJ software to measure the POD of internal carotid artery (ICA) and cortical veins. The average POD of cortical veins (POD ) and the POD difference between ICA and cortical veins (POD ) were calculated. Primary outcome was good functional outcome (modified Rankin scale score of 0-2 at 90 days). One hundred sixty-six patients were finally included in the study. Patients with good functional outcome had lower ipsilateral POD (median [interquartile range (IQR)], 257.198 [216.623-296.631] vs. 290.944 [248.647-338.819], < 0.001) and lower ipsilateral POD (median [IQR], 128.463 [110.233-153.624] vs. 182.01 [146.621-211.331], < 0.001). Multivariable logistic regression analyses showed that ipsilateral POD (odds ratio [OR] 0.991, 95% confidence interval [CI] 0.984-0.999, = 0.019) and ipsilateral POD (OR 0.975, 95% CI 0.963-0.986, < 0.001) were associated with good functional outcome. The predictive ability was significantly enhanced in the model including ipsilateral POD (0.893 vs. 0.842, = 0.027). No correlation was found between ipsilateral POD and expanded Thrombolysis in Cerebral Infarction grades ( = -0.133, = 0.099). Ipsilateral POD is an additional indicator of cerebral reperfusion status and predicts functional outcomes after thrombectomy.